The role of Islamic corporate social responsibility and mediating effect of innovation capability on corporate sustainable longevity in family firms - Ahmad, Shabir (2019)
Though family firms have emerged as a dominant form of business in Pakistan over the years, global competition and domestic environment threaten their very survival like elsewhere in the world. Striving for survival, firms are in constant pursuit of such strategies that could enable them to survive in the long-run. To address the problem, this study intends to develop a model for the family firm’s sustainable longevity. To achieve the objective, a research model was developed which proposes that family involvement in business, Islamic corporate social responsibility (Islamic CSR), and innovation capability (IC) play a vital role in the sustainable longevity of family firms. Based on transaction cost economics (TCE) theory of the family firm, the resource-based theory of the firm and firm survival (RBTFS) and Islamic CSR theory, the research model is composed of seven hypotheses. Prior to model testing, this study developed and validated a measurement scale for corporate sustainable longevity (CSL) by involving 16 field experts in Delphi method and consequently validated the scale through exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) on a dataset of N=200 and N=271, respectively. The research model and hypotheses were tested in Structural Equation Modelling-Partial Least Square (SEM-PLS). By employing judgmental sampling 553 responses were collected through a self-administered questionnaire survey from family firm owners and managers. The findings supported all the hypotheses and validated the model of the family firm’s sustainable longevity. The results indicated that family involvement in business (FIB) and Islamic CSR significantly predict innovation capability and corporate sustainable longevity. Further, the study confirmed that innovation capability partially mediates the relationship between family involvement in business and corporate sustainable longevity. This suggested that owner family’s involvement in the governance and management of the firm (control), commitment, enrichment, and continuity (succession) enhances firm’s innovation capability that in turn enhances its sustainable longevity. Moreover, this study substantiates the important role of Islamic CSR and innovation capability in the corporate sustainable longevity of family firms. Mainly, this study contributes to the body of knowledge by constructing and validating a five-dimensional novel scale of 28 items for corporate sustainable longevity and by developing an integrative model of the family firm’s sustainable longevity. The scale enables managers to anticipate the ability of the firm to sustain longer by examining five functional areas (dimensions) including financial strength, strategic perspective, customer orientation, learning & growth perspective and internal capabilities. The integrative model of family firm’s survival has significant practical implications for the family firms to overcome the survival challenge and devise strategies that lead firm to develop capabilities to sustain longevity. The limitations of this study open new avenues for future researchers to explore external factors that affect firm longevity and to focus on professionally managed family firms instead of owners managed firms.